Strategi Optimalisasi Manajemen Inventaris Dan Penjualan Di Toko SRC FIO - Freony Yuri Silpa; Marsha Anabel Sadina; Riri Monalisa; Sri Laila Ulfa; Vivi Nila Sari (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study examines the primary challenges encountered by SRC FIO Store, a micro, small, and medium enterprise (MSME) involved in the retail of essential commodities. Based on case studies and field observations, three primary issues were identified: inefficient stock and sales management systems, insufficient data for pricing and marketing tactics, and expensive unsold inventory. The research suggests that implementing a digital inventory system, doing sales data analysis, and utilizing forecasting methodologies can address these issues and enhance the profitability and competitiveness of SRC FIO Store.